1986
DOI: 10.1007/bf02059958
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of normalization of Emax for heart size

Abstract: We previously proposed Emax Vd as a normalized form of Emax for heart size relatively independent of wall volume Vm, where Emax is the slope of the end-systolic pressure-volume line and Vd is its volume axis intercept. When Emax Vd remains constant, average circumferential stress for a specified average circumferential strain in the ventricular wall also remains relatively constant, despite changes in Vd/Vm around its normal value. Because accurate determination of Vd is difficult and stress for a given Emax V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Pressure-volume loops combined with variations of preload permit the assessment of the ESPVR, end-diastolic pressure-volume relationship, dead volume, and, in general, the varying elastance curves. Suga and colleagues have shown that the E(t) is fairly independent of loading conditions, contractile state, and HR (31). However, subsequent studies revealed limitations to this simplified theory, such as ESPVR curvilinearity, afterload dependence under certain conditions, and that V o may change during contraction (18,26,29).…”
Section: The Use Of Time-varying Elastance For Assessing Cardiac Funcmentioning
confidence: 99%
“…Pressure-volume loops combined with variations of preload permit the assessment of the ESPVR, end-diastolic pressure-volume relationship, dead volume, and, in general, the varying elastance curves. Suga and colleagues have shown that the E(t) is fairly independent of loading conditions, contractile state, and HR (31). However, subsequent studies revealed limitations to this simplified theory, such as ESPVR curvilinearity, afterload dependence under certain conditions, and that V o may change during contraction (18,26,29).…”
Section: The Use Of Time-varying Elastance For Assessing Cardiac Funcmentioning
confidence: 99%
“…Weber et al [13] observed that systolic stiffness increases with contractility, and they proposed end-systolic stiffness as a contractility index. Suga et al [14,15] proposed a similar index of systolic vigor which might be called hydraulic stiffness, calculated as the slope of the raw end-systolic pressure-volume relation (Era,x) multiplied by the dead space (Va). They remarked [14] that this index (EmaxWo) would not be valid if dead space were acutely variable or if dead space could be negative.…”
mentioning
confidence: 99%